Six o'clock tales - "Blyton, Enid" (Mammoth: London, 1993)
Twinkle the elf fears nothing - until he play a trick on Snorty the dragon and gets the fright of his life! And while Janet and Malcolm go on a thrilling train journey, Tuffy the clown tries to be a hero and Pixie Pinnie paints a cow.
Keywords: Short stories